(3JgfFI Cgd GdESdGe HHfGA HjJ Gddg GdMQGes - (3Gdejehfj , EHQGgje Hf eMeO Hf YjSi, HQgGf GdOjf CHh ESMGb,J (B1079 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Mce HGdJZjQ Ydi cd eNdhb dXghQ fhGejS YXeJg , hGfOc Te GdLHGd ef JLdi LdGd CMOjJg s
(3BNQgG (B:s
(3eHJhQ hBNQ eG ajg (B: (3bGd (B: (3hdG fbd YfOi ai eKdg , GdPi Cbhdg s
(3Cdag Ydi GKQ SbhW LGfH ef GdHjJ GdMQGe SfI (B1039(3g` hHfGDgs
(3hYdi GdfSNI SeGY dNWHI GdcJGH Ydi GdeDda ai MjGJg eDQN (B1065(3g`s
(3GfXQ GjVG Qbe (B1013 (3JGQjNs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B103s
Keywords: (3GdJGQjNs